2014
DOI: 10.21897/rmvz.92
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemical parameters of broilers fed differently thermal processed soybean meal

Abstract: Objective. A 42-days feeding trial was carried out to evaluate the influences of differently thermal processed soybean meal on the broilers blood biochemical parameters. Materials and methods. A total of 200 male birds of Ross strain were allocated into five different diets formulated using differently heat-treated soybean meals, with ten birds per treatment and per replicate. Diets contained: raw soybean (controls), autoclaved for a short (121°C, 20 min; Aut1 group) or medium length period (121°C, 30 min; Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Glucose is an important cellular source of energy and serves as a metabolic substrate [74]. The chicks that were administered probiotic-supplemented diets showed a significant increase (p ≤ 0.05) in their glucose levels and decreased ALT concentrations compared to the chicks in the positive control group.…”
Section: Blood Biochemical Parametersmentioning
confidence: 96%
“…Glucose is an important cellular source of energy and serves as a metabolic substrate [74]. The chicks that were administered probiotic-supplemented diets showed a significant increase (p ≤ 0.05) in their glucose levels and decreased ALT concentrations compared to the chicks in the positive control group.…”
Section: Blood Biochemical Parametersmentioning
confidence: 96%
“…It was concluded that the autoclaving process reduced the MUFA content of the egg yolk compared with raw chickpeas, and microwaving elevated it. In contrast, observed blood serum metabolites indicated reduced lipid metabolism by birds fed heat-treated soybean meal (Nahavandinejad et al, 2014).…”
Section: Resultsmentioning
confidence: 79%
“…Various practices are carried out to remove or reduce the harmful effects of anti-nutritional factors when using legume grains in animal feeds. The goal of thermal processing of grain legumes for poultry nutrition is to increase the nutritional value of the feed and maximize bird performance (Nahavandinejad et al, 2014). These include removing the grain chaff, breaking the integrity of the grain (grinding, crushing), heating (dry heat roasting, cooking in water, steaming), treating with water and various chemical substances, and fermenting (Kaya & Yalcin, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters determined were as follows: glucose, triglycerides, uric acid, total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), HDL to LDL ratio, and alkaline phosphatase. Blood traits were determined based on standard protocols using commercial kits as reported in Nahavandinejad et al [13].…”
Section: Methodsmentioning
confidence: 99%